2021
DOI: 10.51791/njap.v21i1.1142
|View full text |Cite
|
Sign up to set email alerts
|

Pre-and Post-Weaning Phenotypic Relationship Between Some N'dama Cattle Unear Measurements in the Tropics

Abstract: Data collected on 1438 male and 1492 female pure bred N'Dama calves calved between 1948 and 1961 at Fashola Stock farm were used to study the relationship between five N'Dama cattle linear measurements at pre and post Weaning ages. The measurements were Head to Shoulder (HDS); Shoulder to tail drop (STD); Height at withers (HTW); Heart girth (HGT) and Body length (BLT). All measurements had positive values which ranged from 0.2 - 91 except HTW and HDS which had a negative value (-02) in males at yearling age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Sawanon et al (2011) reported the means heart girth and body length of 173.02cm and 136.49cm and, withers height of 124.86cm agreed with the results of the present study and shine circumference of 20.08cm which was lower than that recorded in the present study. Orheruata and Olutogun (1994) reported wide variations in the body measurement of N'dama cattle at different ages. This could have been if data collected were on age basis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sawanon et al (2011) reported the means heart girth and body length of 173.02cm and 136.49cm and, withers height of 124.86cm agreed with the results of the present study and shine circumference of 20.08cm which was lower than that recorded in the present study. Orheruata and Olutogun (1994) reported wide variations in the body measurement of N'dama cattle at different ages. This could have been if data collected were on age basis.…”
Section: Resultsmentioning
confidence: 99%
“…Use of body linear measurements offers advantages over subjective methods of judging cattle such as visual assessment and scoring (Essien and Adesope, 2003).Reports on body weight and linear body measurements had been documented and was found useful in quantifying body size and shape (Ibe and Ezekwe, 1994). Linear body measurements have been used to predict live weights in poultry (Chhabra et al, 1972;Monsi, 1992;Okon et al, 1997;Gueye et al, 1998), goat (Hassan and Ciroma, 1992;Ozoje and Herbert, 1987), sheep (Kandasamy and Gupta, 1983) and cattle (Orheruata and Olutogun, 1994). Body measurements are important data sources in terms of reflecting the breed standards (Riva et al, 2002) and are also important in giving information about the morphological structure and development ability of the animals.…”
mentioning
confidence: 99%